The Two Poverty Enlightenments: Historical Insights from Digitized Books Spanning Three Centuries - Ravallion, Martin (2012)
Word searches of Google's library of digitized books suggest that there have been two "Poverty Enlightenments" since 1700, one near the end of the 18th century and the second near the end of the 20th. The historical literature suggests that only the second came with a widespread belief that poverty could and should be eliminated. After the first Poverty Enlightenment, references to "poverty" (as a percentage of all words) were on a trend decline until 1960, after which there was a striking resurgence of interest, which came with rising attention to economics and more frequent references to both general and specific policies relevant to poverty. Developing countries also became more prominent in the literature. Both Enlightenments came with greater attention to human rights. The written record reflects the push-back against government intervention and the retreat from leftist economics and politics since the late 1970s. Although many debates from 200 years ago continue today, there is little sign that the modern revival of the classical 19th century views on the limitations of government has come with a revival of the complacency about poverty that was common early in that century.